Menilai Kualitas Audit: Pengaruh Reputasi Kantor Akuntan Publik dan Ukuran Perusahaan dengan Masa Tugas Audit sebagai Variabel Moderasi - Sukmawati, Dewi; Junaidi, Junaidi; Purnama, Yunus Indra; Yustisi, Yuni Putri (Penerbit Goodwood, 2024)
Purpose: This study analyzed the influence of Public Accounting Firm (PAF) reputation and company size on the quality of audits, with audit tenure functioning as a moderating variable in the relationship. Methodology: This research utilizes secondary data derived from the annual reports of LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2022. Employing a purposive sampling method, the study generated a sample consisting of 31 companies over an eight-year period. The study employs quantitative methods and moderated regression analysis using the SPSS to test the formulated hypotheses. Results: The findings reveal that PAF reputation has a significant positive effect on audit quality, whereas company size does not demonstrate a notable influence. Additionally, audit tenure weakens the positive relationship between PAF reputation and audit quality, suggesting that extended audit engagements may erode auditor independence and professionalism due to the development of close relationships between auditors and clients. This study emphasizes the intricate dynamics between PAF reputation, company size, and audit tenure in shaping audit quality. The results stress the critical need to uphold auditor independence, particularly in long-term engagements, to ensure robust audit quality. Limitations: This research has limitations concerning the sample, data, and other variables not included in the model. The sample for this study comprises LQ45 entities listed on the Indonesia Stock Exchange (IDX), which may limit the generalizability of the findings to all entities in Indonesia. The secondary data is derived from the publicly available financial statements of these entities, which may pose constraints on the accuracy or completeness of the available data. Contribution: This research provides a theoretical contribution to understanding the complex relationship between the reputation of public accounting firms, entity size, and audit quality, with audit tenure serving as a moderating variable.